Rheology, morphology, and mechanical properties of reactive compatibilized polypropylene/polystyrene blends via Friedel–Crafts alkylation reaction in the presence of clay. Issue 1 (25th September 2015) - Abbasi, Fatemeh; Tavakoli, Akram; Razavi Aghjeh, Mir Karim
Abstract : Attempts were made to study the effect of reactive compatibilization via Friedel–Crafts alkylation reaction, using AlCl3 as a catalyst, on rheology, morphology, and mechanical properties of polypropylene/polystyrene (PP/PS) blends in the presence of an organoclay (Cloisite 15A). During the reactive compatibilization process, PS showed much more degradation than that of PP in the presence of AlCl3 . It was found that the effect of generation of PP‐ g ‐PS copolymer at the interface of the PP/PS blend dominates the effects of degradation of PS and PP phases, which manifested itself by increased toughness as well as uniform dispersion of the dispersed PS particles in the PP matrix. Generation of PP‐ g ‐PS copolymer was confirmed by using Fourier‐transform infrared analysis. By using rheological and X‐ray diffraction analyses, it was shown that the clay had higher affinity to PS than that of PP. It was also shown that the clay located at the interface of PP and PS phases, leading to increased relaxation time of the deformed PS dispersed particles, exhibited higher dispersion in PP/PS blend, which resulted in higher ductility of the blend. By using the results of rheological studies, it was concluded that during reactive compatibilization of the blend nanocomposite, the clay migrated into the dispersed PS phase, which was confirmed by scanning electron microscopy analysis. It was demonstrated that the rheological studies have a reliable sensitivity to the clay partitioning and phase morphology of the studied blends and blend nanocomposites . J. VINYL ADDIT. TECHNOL., 24:18–26, 2018. © 2015 Society of Plastics Engineers